SKYHOOK Churchill 1973. - Pappas,Tom; White,Paul S. (1974)
The program was funded to conduct balloon field operations from Fort Churchill, Manitoba and from Thompson, Manitoba, Canada. The contract also called for the delivery of three balloons to be used in the program. Raven provided a field crew, suspension and rigging hardware, aircraft and helicopter tracking, parachutes, balloon telemetry and control instrumentation, electronic tracking, and reports and documentation as necessary. This report describes individual flights, equipment used, flight data, and various program information. (Author) See also AD-732 483.